Vertebrates show coordinated elevated expression of mitochondrial and nuclear genes after birth - Medini, Hadar; Mishmar, Dan (Genome Research, 2025)
Interactions between mitochondrial and nuclear factors are essential to life. Nevertheless, the importance of coordinated regulation of mitochondrial–nuclear gene expression (CMNGE) to changing physiological conditions is poorly understood and is limited to certain tissues and organisms. We hypothesized that CMNGE is important for development across vertebrates and, hence, should be conserved. As a first step, we analyzed more than 1400 RNA-seq experiments performed during prenatal development, in neonates, and in adults across vertebrate evolution. We find conserved sharp elevation of CMNGE after birth, including oxidative phosphorylation (OXPHOS) and mitochondrial ribosome genes, in the heart, hindbrain, forebrain, and kidney across mammals, as well as in Gallus gallus and in the lizard Anolis carolinensis. This is accompanied by elevated expression of TCA cycle enzymes and reduction in hypoxia response genes, suggesting a conserved cross-tissue metabolic switch after birth/hatching. Analysis of about 70 known regulators of mitochondrial gene expression reveals consistently elevated expression of PPARGC1A (also known as Pgc-1alpha) and CEBPB after birth/hatching across organisms and tissues, thus highlighting them as candidate regulators of CMNGE upon transition to the neonate. Analyses of Danio rerio, Xenopus tropicalis, Caenorhabditis elegans, and Drosophila melanogaster reveal elevated CMNGE prior to hatching in X. tropicalis and in D. melanogaster, which is associated with the emergence of muscle activity. Lack of such an ancient pattern in mammals and in chickens suggests that it was lost during radiation of terrestrial vertebrates. Taken together, our results suggest that regulated CMNGE after birth reflects an essential metabolic switch that is under strong selective constraints.
10.1101/gr.279700.124